The future of the euro: Is there an alternative to the stability and growth pact? - Philip Arestis; Kevin McCauley; Malcolm Sawyer (Levy Economics Institute of Bard College, 2001)
This brief provides a detailed description of the Stability and Growth Pact, an agreement entered into by the member states of the European Union that has far-reaching implications for the long-run value of the euro, and therefore, on the real economy in terms of output growth and employment. Yet despite the fact that the pact underpins the adoption of the single currency and has fundamentally redefined the scope and nature of economic policymaking in the member states, public discussion about it is relatively scant, especially on our side of the Atlantic, even though the economic health of the European Union does matter to the economic and strategic position of the United States. The authors provide propose a critique of the pact that focuses on the shortcomings induced by the its regime of mandatory fiscal austerity, the separation between fiscal and monetary policy, the undemocratic structure and lack of accountability of the European Central Bank, and the paramount importance attached to price stability at the expense of other policy objectives. According to the authors, these shortcomings will have serious negative effects on the current and future economic performance of the member states and the material well-being of its citizens.
Keywords: 330; EU-Stabilitätspakt; Euro; Europäische Wirtschafts- und Währungsunion; Geldpolitik; EU-Staaten